Few-layer bismuthene for femtosecond soliton molecules generation in Er-doped fiber laser. (9th November 2018) - Wang, Chong; Wang, Lu; Li, Xiaohui; Luo, Wenfeng; Feng, Tianci; Zhang, Ying; Guo, Penglai; Ge, Yanqi
Abstract: Bismuthene, a mono-elemental two-dimensional material with a novel kind of few-layer structure purely consisting of bismuth, has been predicted to have a prominent optical response and enhanced stability in theory. In this paper, few-layer bismuthene is employed as the saturable absorber. The mode-locker is fabricated by dropping bismuthene on a microfiber in a passively mode-locked, Er-doped fiber laser. The single pulse can be obtained at 122.1 mW, with 621.5 fs pulse duration at 1557.5 nm central wavelength, 10.35 nm spectral width and fundamental repetition of 22.74 MHz. Thanks to the outstanding nonlinear effect and semimetal of the bismuthene, dual-pulses, octonary-pulses and fourteen-pulses soliton molecules with tightly and loosely temporal separation can be achieved for the first time, to the best of our knowledge. The preceding indicates that bismuthene will have wide potential in many applications, such as optical fiber communications, optical logical gate, and laser materials processing, etc.